2005
DOI: 10.1111/j.1442-9071.2005.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the accuracy of Orbscan II post‐LASIK: apparent keratectasia is paradoxically associated with anterior chamber depth reduction in successful procedures

Abstract: Using the Orbscan II device, the forward protrusion of the posterior corneal surface appears to coincide with a paradoxical reduction in depth of the anterior chamber. Although the keratectasia found in this study is accompanied by thin postoperative corneas and larger central pachymetry change, the contradictory decrease in anterior chamber depth creates uncertainty of measurement, and of ectasia as a mechanism of regression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 34 publications
3
43
0
Order By: Relevance
“…Cairns et al 15 found the mean post-LASIK follow-up was 8.3 G 4.0 weeks, a period similar to our 4-to 8-week follow-up analysis.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Cairns et al 15 found the mean post-LASIK follow-up was 8.3 G 4.0 weeks, a period similar to our 4-to 8-week follow-up analysis.…”
Section: Discussionsupporting
confidence: 81%
“…Baek et al 7 found a mean forward shift of as much as 40.9 G 24.8 mm in a retrospective review of 196 eyes after LASIK. Cairns et al 15 found a mean forward protrusion of approximately 20 mm in 154 post-LASIK eyes. Our study found a mean forward shift of only 2.64 G 4.95 mm.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This hypothesis might explain why some studies found paradoxical findings; that is, an increase in central posterior elevation, interpreted in most studies as a forward bulging of the posterior cornea, and a decrease in anterior chamber depth. 24 Regarding the clinical relevance of the posterior surface changes after surgery, we found that the maximum change in the central posterior cornea occurred in Group 1 after 1 day and reached À0.106 D, corresponding to a decrease in radius of curvature of 96 mm. This change is too small to have a clinical impact on refraction.…”
mentioning
confidence: 96%
“…8,17 Whether this bulging is real or an optical phenomenon is still being debated. [37][38][39][40] Although direct confirmation is not yet available, indirect evidence of ectasia has been proposed. Several authors have shown this ectasia to be correlated with the residual bed thickness 9,10,13 and/or manifest refraction.…”
Section: Discussionmentioning
confidence: 99%